Enhanced Pulmonary Arteriopathy in Simian Immunodeficiency Virus–infected Macaques Exposed to Morphine - Spikes, Leslie (American Thoracic Society, 2012)
Rationale: HIV-associated pulmonary arterial hypertension (PAH) is likely a more prevalent noninfectious complication of AIDS than previously recognized. Furthermore, the majority of HIV-PAH cases occur in individuals with a history of intravenous drug use. In this study we used a simian immunodeficiency (SIV) macaque model and a primary cell-culture system to investigate the association between drug abuse and HIV infection in HIV-PAH development. Methods: The archival lung tissues from macaques previously used to study the effect of morphine on SIV infection–associated neuropathogenesis were analyzed for pulmonary vascular changes. The direct effect of HIV proteins and illicit drugs was investigated on oxidative stress, survival, and proliferation of human pulmonary microvascular endothelial cells. Measurements and Main Results: SIVmacR71/17E-infected rhesus macaques treated with morphine (VM group) demonstrated significant pulmonary vascular remodeling, including the presence of early and advanced complex (plexiform) lesions, when compared with either the SIV-infected (V group) or morphine-treated uninfected (M group) macaques. However, both the V (two of five) and VM (two of six) groups included some animals with Pneumocystis jirovecii pneumonia. The endothelial cells lining the vessels with medial hypertrophy or initial-stage intimal lesions in lung sections from VM macaques demonstrated an increase in positivity for both terminal dUTP nick-end labeling and Ki67. Oxidative stress–mediated enhanced apoptosis followed by enhanced proliferation of endothelial cells was observed on simultaneous treatment with viral proteins and drugs of abuse compared with either treatment alone. Conclusions: Our findings suggest that SIV/HIV protein(s) and morphine interact to cause the proliferation of apoptosis-resistant endothelial cells leading to angio-obliteration.